Pentingnya Memahami Karakteristik Siswa Sekolah Dasar di SDN Cikokol 2 - Nevi Septianti; Rara Afiani (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2020)
This study is based on the existence of learning activities that are less responsive to various individual characteristics. To meet these demands, teachers need to understand students' characteristic. If the teacher in delivering the lesson material less attention to the characteristics of the students and the personality traits of students is not used as a foothold in learning, students will have difficulty understanding the subject matter. Whatever efforts are chosen and performed by the teacher and the lesson designer if they are not based on individual characteristics of the student as subject of learning, then the developed learning will not be meaningful for the students. Characteristics of students is very important to know by educators, because it is very important to be a reference in formulating learning strategies. Learning strategy is developed by teachers and implemented through learning methods to the students so that the learning objectives can be achieved effectively and efficiently. This research uses qualitative descriptive approach and data collection techniques used are interview, observation, and documentation in SDN Cikokol 2.